Determinants of hospital death in haematological cancers: findings from a qualitative study. Issue 1 (29th June 2017) - McCaughan, Dorothy; Roman, Eve; Smith, Alexandra G; Garry, Anne; Johnson, Miriam; Patmore, Russell; Howard, Martin; Howell, Debra A
Abstract : Objectives: Current UK health policy promotes enabling people to die in a place they choose, which for most is home. Despite this, patients with haematological malignancies (leukaemias, lymphomas and myeloma) are more likely to die in hospital than those with other cancers, and this is often considered a reflection of poor quality end-of-life care. This study aimed to explore the experiences of clinicians and relatives to determine why hospital deaths predominate in these diseases. Methods: The study was set within the Haematological Malignancy Research Network (HMRN—www.hmrn.org ), an ongoing population-based cohort that provides infrastructure for evidence-based research. Qualitative interviews were conducted with clinical staff in haematology, palliative care and general practice (n=45) and relatives of deceased HMRN patients (n=10). Data were analysed for thematic content and coding and classification was inductive. Interpretation involved seeking meaning, salience and connections within the data. Results: Five themes were identified relating to: the characteristics and trajectory of haematological cancers, a mismatch between the expectations and reality of home death, preference for hospital death, barriers to home/hospice death and suggested changes to practice to support non-hospital death, when preferred. Conclusions: Hospital deaths were largely determined by the characteristics of haematological malignancies, which included uncertain trajectories, indistinct transitions and difficulties predicting prognosis and identifying if or when to withdraw treatment. Advance planning (where possible) and better communication between primary and secondary care may facilitate non-hospital death.